Game Based Learning for Autism in Learning Mathematics - Che Ku Nuraini Che Ku Mohd, Faaizah Shahbodin, Muliati Sedek, Munirah Samsudin (International Journal of Advanced Science and Technology, 2020)
In the 21st century, research related to a game-based learning (GBL) have attracted many researchers and practitioners in researching more on the matters. Due to the positive effects of game-based learning, numerous studies have led more researchers to create educational games in supporting the teaching and learning development in schools especially for the need of the 21st century students. Moreover, students also realize the benefits gained while dealing with a game-based learning as well as the acquisition of 21st-century skills. Therefore, the purpose of this study is to develop a game-based learning for autistic children in learning basic mathematics. Through this game, the autistic children will learn mathematic in a structured and easier way. Some simple notes will be provided for them. The notes will act as a manual or guide before they attempt the games. For this study, the quantitative methods have been employed. Meanwhile, the ADDIE model has been embedded in developing this game-based learning. The respondents chose were primary school students aged 5 to 8 years old. The testing was conducted among autism students from Melaka Autism Education Centre. The expected outcome of GBL is to attract autism children to learn and focus during learning process. Besides that, GBL has also been found to be able to motivate students in learning and, it has been agreed by all that using GBL is the most effective teaching strategy to promote learning. Keywords: Autism, Game Based Learning, Multimedia, Mathematics, 21st Century Skill, Technology